EKSISTENSI TRADISI KERTAS GEDHOG DALAM KEHIDUPAN SOSIAL BUDAYA MASYARAKAT TEGALSARI PONOROGO - Andhita Risko Faristiana; Muhammad Irham Ibrahim; Dhafa Ahsanul Hudda; Vina Risda Khoirotunnisa (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2026)
This study aims to examine the social and cultural role of the Dzuriyah of Tegalsari in preserving the gedhok paper tradition in Tegalsari, Ponorogo, and to understand its meaning, practices, and preservation challenges in the modern era. The research employs a qualitative approach with an ethnographic method through observation and in-depth interviews with the Head of Tegalsari Village and Mr. Sawir as key informants. The findings show that gedhok paper is a cultural heritage closely linked to the literacy history of the Tegalsari Islamic boarding school and is still maintained through traditional production processes, raw material conservation, manuscript reproduction, and cultural socialization activities. The Dzuriyah of Tegalsari plays a central role in sustaining this tradition by transmitting cultural values, knowledge, and practices. However, the preservation faces challenges such as digital technological advancement, limited raw materials, low youth interest, and shifting economic orientation. The study concludes that the sustainability of the gedhok paper tradition requires collaboration between the community, local government, and younger generations to maintain it as a local cultural identity.